The Holy Week Rites of the Mananambal of Siquijor - Mascunana, Rolando V.; Pioquinto, Ceres E.; Schales, Christian K. (Silliman Journal, 2022)
Intended as an introductory piece to tthe series of articles on traditional healing practices of the mananambal or shamnistic healers of Siquijor, this paper documents the rites and rituals observed by the traditional healers during Holy Week. Rooted in the folk belief that the spirit world opens on Good Friday and magical powers are dispensed into the environment, holy Week is thus the most eventful activity of the year for the mananambal of Siquijor who host this event, as well as for visiting mananambal from other islands. Aside from the ritual search for medical materials that climaxes on Good Friday, the highlight of this celebration is the ritual cooking of two of the most important concoctions of the tradional healing practice: the igdalaut or evil brew used in sorcery and prepared during Good Friday, and the minasa or antidote to sorcery cooked during Black Saturday. Given the widespread popularity of this annual event among traditional healers, it is not surprising that the Siquijor Holy Week rites attract not only oldtimers but new faces as well. Predictably, the entry of television and film has given these once hallowed rituals both national and international attention, attracting even more followerrs and believers in the process. As yet, it is difficult to gauge the extent of media influence on these practices but one thing is certain, some of the mananambal themselves seemed to have understood fully the implication of media presence to their reputation and appeared to have taken advantage of this media exposure to add a bit of show effects on their rituals.